Economics of Smokeless Tobacco (SLT) in India - Monga, Divya; Prinja, Shankar (Indian Journal of Community Health, 2018)
Despite the high prevalence of Smokeless Tobacco (SLT) in India, cost-effective interventions to curb smokeless tobacco use are very low. Taxation is considered as one of the most cost-effective intervention to curb overall tobacco use but taxation on SLT product is very complex and is on ad-valorem basis. Further, Goods and Service Tax has increased the price from 0.8/gram to 1.06/gram, but still the impact of increasing the tax needs to be explored so that harmony between excise revenue generated from these products and decrease in demand of these products can be maintained. Therefore, we carried out a literature review, which involved literature search, data extraction, and synthesis. The evidence suggests that the price elasticity of SLT products has gone closer to the inelastic nature with the passing time suggesting the increasing affordability of these products. The macroeconomic impact of the disease burden resulting from these SLT products is far greater than excise revenue generated by these products. More research is required in this field with updated data. The agricultural aspect of SLT products also need to be explored to determine cost-effective alternative crops for tobacco farming. Also, as the use of SLT is culturally accepted in India, appropriate public awareness program and cost-effective interventions are required to curb SLT use along with increased tax and cessation services.